Holt-Oram syndrome revisited. Two patients in the same family - José Dario Frota Filho; Wagner Pereira; Tiago Luiz Luz Leiria; Mario Vallenas; Paulo E. Leães; Celso Blacher; Eraldo Lúcio; Fernando A. Lucchese (Arquivos Brasileiros de Cardiologia, 1999)
Holt-Oram syndrome was first described in 1960 as an association of familial heart disease and musculoskeletal abnormalities. The most important findings include atrial septal defects, atrioventricular conduction abnormalities, vascular hypoplasia, and upper limb musculoskeletal deformities. We report two patients with this syndrome in the same family and discuss the variability of the musculoskeletal abnormalities and their association with the cardiac morphologic defects. Both patients in this study had associated eosinophilia, which has not been reported in the literature.